Introduction: I See Black People - Smith-Shomade, Beretta E. (Watching While Black, 2012)
This project has been engaging my thoughts for nearly a decade. I was forced to actually address it while sitting in our temporary home in Ile-Ife, Nigeria, watching world satellite TV with virtually no Blacks on it. In Nigeria, I became acquainted with Paris-based Fashion TV, U.S.-based Style Network, and the Australian production McLeod’s Daughters. Outside of M-Net’s Africa Magic, a network dedicated to showing Nollywood productions primarily, television was anything but Black. This whitening of the televisual frame, even in Black Africa, made me begin to consider the dearth of knowledge circulating about Black television programming, even when abundance
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Shaded Lives: African-American Women and Television - Smith-Shomade, Beretta E. (Rutgers University Press, 2002)
Since its invention, television has been one of the biggest influences on American culture. Through this medium, multiple visions and disparate voices have attempted to stake a place in viewer consumption. Yet even as this programming supposedly reflects characteristics of the general American populace, television-generated images are manipulated and contradictory, predicated by the various economic, political, and cultural forces placed upon it. In Shaded Lives, Beretta Smith-Shomade sets out to dissect images of the African American woman in television from the 1980s. She calls their depiction "binaristic," or split. African American women, although an essential part of television programming today, are still presented as distorted and deviant. By closely examining the television texts of African-American women in comedy, music video, television news and talk shows (Oprah Winfrey is highlighted), Smith-Shomade shows how these voices are represented, what forces may be at work in influencing these images, and what alternate ways of viewing might be available. Smith-Shomade offers critical examples of where the sexist and racist legacy of this country collide with the cultural strength of Black women in visual and real-lived culture. As the nation's climate of heightened racial divisiveness continues to relegate the representation of Black women to depravity and display, her study is not only useful, it is critical.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

"Rock-a-Bye, Baby!": Black Women Disrupting Gangs and Constructing Hip-Hop Gangsta Films - Smith-Shomade, Beretta E. (Cinema Journal, 2003)
This essay examines the cultural specificity of the gangster genre. In hip-hop gangsta films, the inclusion of black women as central to the gangster business not only transforms the gangster genre but, more important, adheres to black cultural norms. The films New Jack City, Sugar Hill, and Set It Off serve as case studies.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Pimpin' Ain't Easy: Selling Black Entertainment Television - Smith-Shomade, Beretta E. (Routledge, 2007)
Launched in 1980, cable network Black Entertainment Television (BET) has helped make blackness visible and profitable at levels never seen prior in the TV industry. In 2000, BET was sold by founder Robert L. Johnson, a former cable lobbyist, to media giant Viacom for 2.33 billion dollars. This book explores the legacy of BET: what the network has provided to the larger US television economy, and, more specifically, to its target African-American demographic. The book examines whether the company has fulfilled its stated goals and implied obligation to African-American communities. Has it changed the way African-Americans see themselves and the way others see them? Does the financial success of the network - secured in large part via the proliferation of images deemed offensive and problematic by many black communities - come at the expense of its African-American audience? This book fills a major gap in black television scholarship and should find a sizeable audience in both media studies and African-American studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

“Regular Television Put to Shame by Negro Production”: Picturing a Black World on Black Journal - Heitner, Devorah (Watching While Black, 2012)
In the first episode of Black Journal , before the opening credits, comedian Godfrey Cambridge appears dressed in overalls and a painter’s cap with a paint roller in hand and methodically paints the television frame. To the viewer, it appears that his or her television is being painted black from the inside—a potent visual symbol from the first national Black public affairs program. Initially, though, the symbol emphasizes a visual challenge to the absence of Black faces on television—a show that “looks” Black, because of the visibility of its Black hosts and reporters, but where whites still have significant
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Gimme a Break! and the Limits of the Modern Mammy - Fuller, Jennifer (Watching While Black, 2012)
Picture this: a comedy about an overweight Black woman who lives with and takes care of a white family. Joking all the way, she cooks, cleans, helps the father of the family, and comforts the children. Then at one point, we see the father holding his gun and pointing toward the door. The Black woman enters and jumps up and down, screaming, “Massa! Massa! Massa! Please don’t shoot!” It is easy to imagine these scenes in a 1930s film about the antebellum South. But they are actually from the first episode of a 1980s sitcom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Keepin’ It Reality Television - Gates, Racquel (Watching While Black, 2012)
On November 4, 2008, CNN anchor Anderson Cooper appeared on The Ellen DeGeneres Show via satellite. One of the more memorable moments of the interview came when Cooper expressed shock that DeGeneres was unfamiliar with the hit Bravo television show The Real Housewives of Atlanta. “You mean you don’t know about NeNe?” he demanded incredulously, referring to cast member NeNe Leakes—the most outspoken and self-proclaimed “realest” of the Housewives. Cooper’s segment, along with his admission that Leakes was his favorite of the cast, brought even more attention to the already widely debated show, the first of Bravo’s Housewives series
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Prioritized: The Hip Hop (Re)Construction of Black Womanhood in Girlfriends and the Game - Lewis, Nghana (Watching While Black, 2012)
Why is it important that a Black woman created, wrote for, and co-produced¹ two highly-regarded television situation comedies that engaged a variety of Black women’s health issues while at the same time these issues were being reduced, simplified, or altogether ignored in mainstream American hip hop? Mara Brock Akil tacitly responded to this question when asked why four episodes of the third season of Girlfriends (2000–2008), the situation comedy she created and co-produced for UPN, addressed the HIV/AIDS crisis among Black women in America. “I have things I want to say,” explained Brock Akil, “about bridging television’s gap between
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Minority Television Trade as Cultural Journey: The Case of New Zealand’s Bro’Town - Havens, Timothy (Watching While Black, 2012)
Four animated, brown-skinned youth are lounging on a porch step in Auckland, New Zealand, when a fierce-looking social worker and police constable approach and insist on knowing where the father of two of the boys is. As the constable raises his nightstick, one of the boys fumbles in heavily accented Māori English, “He went to the pub four days ago and hasn’t been back.” The authorities quickly cart two of the boys off as wards of the state as another performs a Māori haka, or war chant, in mock warning to the police.
Keywords: 1-TV; 2-Approches sociologiques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Nouvelle-Zélande/Aotearoa (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

“Hey, Hey, Hey!”: Bill Cosby’s Fat Albert as Psychodynamic Postmodern Play - Russworm, TreaAndrea M. (Watching While Black, 2012)
Although the cartoon series Fat Albert and the Cosby Kids (CBS, 1972–1984) averaged only nine new episodes a year during its twelve-year run (compared to a more standard production cycle of twenty-five to sixty new episodes a year for other cartoons), the show remained a highly popular option for young viewers on late Saturday mornings. By the time of the series’ network premiere in 1972, the cartoon’s animated African American stars—Weird Harold, Dumb Donald, Fat Albert, Rudy, Mushmouth, Bucky, Russell, and Bill—were familiar and recognizable to American audiences as originating from Bill Cosby’s boyhood community of North
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Down in the Treme … Buck Jumping and Having Fun?: th Impact of Depictions of Post-Katrina New Orleans on Viewers’ Perceptions of the City - LeDuff, Kim M. (Watching While Black, 2012)
Five years after Hurricane Katrina devastated New Orleans, Louisiana, life remained not normal still for many residents of the city. And while mainstream news organizations remembered the fifth anniversary of the hurricane with extensive coverage, it was the work of filmmaker Spike Lee and television program creators David Simon and Eric Overmyer that perhaps created the greatest buzz about the fifth anniversary of Katrina in 2010. Spike Lee’s first documentary, When the Levees Broke , was released in 2006. It documented what happened in New Orleans through the voices of local residents, politicians, and experts during and immediately after the storm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Nigger, Coon, Boy, Punk, Homo, Faggot, Black Man: Reconsidering Established Interpretations of Masculinity, Race, ans Sexuality Through Noah’s Arc - Cunningham, Mark D. (Watching While Black, 2012)
At best, our knowledge about the lives and experiences of Black gay men is limited to a series of stereotypes, snap judgments, and ridicule. In terms of television media product, this aforementioned knowledge has been packaged mostly within the framework of comedy: a red-leather-clad Eddie Murphy talking about the most effective ways to shield his ass from the gay male gaze in the 1983 HBO stand-up performance Delirious ; Damon Wayans and David Alan Grier’s effeminate film critics Blaine Edwards and Antoine Merriweather on the 1990s television variety show In Living Color ; fashionista panel members Miss J and Andre Leon Talley
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Graphic Blackness/Anime Noir: Aaron McGruder’s the Boondocks and the Adult Swim - Whaley, Deborah Elizabeth (Watching While Black, 2012)
Aaron McGruder’s “The Return of the King” (2006) is one of many of the artist’s controversial episodes, yet it stands out because of the criticism it received among mainstream media outlets and civil rights leaders. It was the ninth episode to air from his series The Boondocks, which is an anime show that airs on the Cartoon Network’s Adult Swim cable channel. McGruder presents the following scenario in “The Return of the King”: What if Martin Luther King Jr. (MLK) did not die after his April 4, 1968, shooting and instead awoke after being in a coma for thirty-two years?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Resistance Televised: The TV da Gente Television Network and Brazilian Racial Politics - Gillam, Reighan Alexandra (Watching While Black, 2012)
As activists and political leaders in Brazil call for increasing rights, recognition, and redress to address the multiple forms of marginalization that Afro-Brazilians have endured, media has become an increasingly important sphere through which different constituencies mobilize to advance a project of racial equality. Among these groups enlisting available media resources was a group composed predominately of Afro-Brazilian media professionals who joined together to launch the TV da Gente (Our TV) television network, Brazil’s first television station with the mission to produce racially diverse programming directed toward a Black viewing audience.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

South African Soapies: A “Rainbow Nation” Realized? - Burton, Nsenga K. (Watching While Black, 2012)
In the United States, daytime soap operas are often critiqued as escapist fantasies with narratives that provide leisure and pleasure for middle-class and stay-at-home mothers. The storylines typically involve forbidden sexual liaisons and business relationships, with physical and psychological behaviors that center on powerful families. One family unit usually represents “old money” while the other family represents “new money” or an upwardly mobile group with aspirations of power, status, and influence. The economic differences are usually the source of conflict between the families, around which all other social relationships develop. The temporal space expands and contracts to accommodate storylines, which
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Two Different Worlds: Television as a Producer’s Medium - Coleman, Robin R. Means; Cavalcante, Andre M. (Watching While Black, 2012)
Although discourses regarding 1980s representations of Blackness on television heavily focus on The Cosby Show, its NBC spin-off series, A Different World, depicting student life at a historically Black college, was equally groundbreaking and deserving of critical attention. Looking to transfer the appeal and audience share of The Cosby Show to A Different World, the spin-off show’s first season centered on the life of The Cosby Show’s star Denise Huxtable (Lisa Bonet) at Hillman College. A Different World’s story provides an illuminating case study of the role and power of television producers, highlighting their influence over a show’s narrative and
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé)